Implementing a new power aware routing algorithm based on existing dynamic source routing protocol for mobile ad hoc networks. Issue 2 (1st June 2014) - Shivashankar; Varaprasad, Golla; Hosahalli Narayanagowda, Suresh
Abstract : Energy consumption is a crucial design concern in mobile ad hoc networks (MANETs), since nodes are powered by batteries with limited energy, whereas in existing dynamic source routing (DSR) does not take the energy limitation of MANET nodes into account. In this study, the authors propose an efficient algorithm for MANETs, which maximises the network lifetime by minimising the power consumption while establishing path with the help of modified DSR. The proposed work minimises the energy consumption per packet and maximises the network lifetime. The design objective of modifying DSR is to select energy‐efficient paths. The main features of modified DSR are: (i) minimise energy consumed per packet (ii) maximise network lifetime for network and (iii) minimise maximum node cost. However, some intermediate nodes might act selfish and drop the packets for other nodes in order to save their own battery power. The proposed algorithm can find selfish nodes and deal with them by using a modified DSR protocol, which we call as an efficient DSR (EDSR). The simulation results show an increase in the packet delivery ratio in the network. The average node lifetime of proposed EDSR model is 45–60% longer than that of DSR model.